Роль пероксидази у формуванні індукованої стійкості рослин пшениці за допомогою імуномодуляторів - Жук, І.В.; Дмитрієв, О.П.; Лісова, Г.М. (Фактори експериментальної еволюції організмів, 2016)
Aim. The usage of biological elicitors for plant defense responses against plant pathogenic fungi may initiate tolerance of
plants and prevent environmental pollution. The aim of research was to investigate the role of peroxidase under combined
action of oxalic acid and NO in elicitation of wheat systemic defense responses against Septoria tritici blotch agent in
field trials. Methods. The peroxidase activity was measured in leaves of elicitor-treated winter wheat plants (cv. Poliska
90 and Stolychna) after S. tritici blotch inoculation during ontogenesis. The morphometric parameters, extent of disease
development and yield structure were analyzed. Results. The data obtained suggest that oxalic acid induced in both wheat
cultivars (Stolychna and Poliska 90) defense responses against S. tritici blotch agent. Initiation of defense responses in
elicitor-treated plants occured shortly. The effect of oxalic acid treatment increased the hydrogen peroxide content. The
effect of oxalic acid also increased the grain quantity and plant height. Conclusions. Elucidation of biochemical nature of
the defense responses elicitation revealed increased peroxidase activity for lignin synthesis and mechanical strengthening
of the plant cell walls.
Keywords: peroxidase, oxalic acid, NO, Triticum aestivum L., Septoria tritici.